Prognostic factors for medicamentous and dental treatment failure in odontogenic sinusitis - Dwiyani, Kartika; Safitri, Eka Dian; Manalu, Josua (PERHATI-KL, 2025)
Background: Odontogenic sinusitis refers to bacterial maxillary sinusitis caused by maxillary dental pathology, or complications from dental procedures. The therapeutic algorithm usually has two stages: conservative and surgical. If conservative therapy alone is successful in curing sinusitis, unnecessary sinus surgery can be avoided. But if conservative therapy fails, sinus surgery is usually required to remove the cause of the pathology. The effectiveness of conservative therapy varies in the range from 36 to 95%. Purpose: To investigate prognostic factors for medicamentous and dental treatment failure in odontogenic sinusitis. Case illustration: A 27 years old male with odontogenic sinusitis should undergo endoscopic sinus surgery although he had already received optimal conservative therapy. Clinical question: In patients with odontogenic sinusitis treated by conservative therapy, are smoking habits, high total Lund-Mackay score including osteomeatal complex (OMC) blockage, and history of dental procedure contribute as prognostic factors for medicamentosa and dental treatment failure? Method: Literature searching was performed through PubMed, Cochrane database and Hand-searching using keyword “odontogenic sinusitis”. Result: Three valid prognostic cohort articles were appraised for the validity, importance, and applicability in our clinical scenario. The precision prognostic factor is high total Lund-Mackay score with odd ratio (OR) 95%, and confidence interval (CI) 2.0, 1.04-3.79. Conclusion: High total Lund-Mackay score is an important prognostic factor for conservative therapy failure, so that the sinus surgery should be performed.